Role of pretest counseling sessions on increasing subjective knowledge about HIV and hepatitis transmission among the beneficiaries of a free of charge, voluntary counseling and testing program in Constanta, Romania. (28th February 2018) - Schweitzer, A‐M; Bogdan, M; Corduneanu, A; Ciocea, I
Abstract : Objectives: To describe the characteristics of clients who enrolled into of an opt‐in, HIV, HBV & HCV Voluntary Counseling and Testing Program in Dobrogea Region, Romania (VCT) and to identify the utility of the pre‐test counseling sessions in increasing subjective perception regarding transmission knowledge for the clients attending the VCT program. Methods: Cross sectional data collection, between August 2015 and September 2016. Sociodemographic and behavioral information were collected for the clients who enrolled at two Baylor centers. Counselors were trained regarding the delivery of standardized information during the session, to reduce variation. After the pre‐test session clients evaluated the subjective level of knowledge (SK) increase regarding viral transmission. Results: 3065 clients were screened at the two centers and completed the SK increase assessment after the pre‐test session. About 9% of all persons tested had reactive results to any of the infections in the context of high exposure risks for 62% and low hepatitis B vaccination rates (8%). 78% of attendees perceived that their knowledge regarding HIV and viral hepatitis transmission increasing with more than 60% as the result of the pretest counselling; more information was gained about hepatitis transmission compared with HIV. Conclusion: Cumulative prevalence in Dobrogea community is high. The NGO‐run VCT program is helping the healthcare system to efficiently screen for undiagnosed HIV and hepatitis cases. Pre‐test counselling is directly contributing to increasing SK among attendees. Routine HIV and hepatitis integrated pre‐test counseling should be considered as a good‐practice even in settings where it is not compulsory by law.